Dampak Employee Stock Option (ESO) Terhadap Abnormal Return pada Perusahaan Terdaftar di Bursa Efek Indonesia: Analisis Peran Corporate Governance sebagai Pemoderasi - Rizani, Ahmad; Judijanto, Loso; Setiadi, Sandi; Iswanto, Juni (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2023)
The purpose of this study is to examine how employee stock options (ESOs) affect abnormal returns while controlling corporate governance. Institutional ownership, management ownership, and independent commissioners are the corporate governance proxy variables that are employed. Using a purposive sample technique, the research sample was made up of businesses that were listed between 2015 and 2020 on the Indonesia Stock Exchange. Data from the 20 sample companies were analyzed using moderated regression analysis (MRA). The findings of the study indicate that employee stock options (ESOs) have a major impact on abnormal returns, and that corporate governance plays a crucial moderating role in controlling the relationship between ESOs and abnormal returns. These findings provide a better understanding of the dynamics between ESOs, corporate governance, and corporate financial performance in the Indonesian capital market.